Social networks and the teaching of literature: a reflection on the notion of authorship - Rosa, Maria Eneida Matos da (Revista de Letras, 2019)
The article entitled “Redes sociais e o ensino de literatura: uma reflexão sobre a noção de autoria” aims to understand the influence of new tech media by analyzing indiscriminate use of writers’ quotes in social networks. The goal is to check if it’s possible to use such influence to stimulate reading habits in the classroom. The mentioned research examines why authors like Caio Fernando Abreu and Clarice Lispector are so popular in cyberspace and if this virtual preference has any reflex in the offline life of the readers. In order to come to a conclusion, it’s necessary to deal with concepts related do cyberspace, hypermedia and hypertext by authors like Pierre Lévy and Umberto Eco, as well as reading and readers formation by the use of literature in class.